The Correlation Between Essential Amino Acid Tryptophan, Lysine, Phenylalanine and Chemotherapy of Breast Cancer - Yafeng Lv MM; Xuan Yang MM; Ying Song MM; Dechun Yang MM; Kai Zheng MD; Shaoqiang Zhou MD; Hanhui Xie MM; Rong Guo MD; Shicong Tang MD (Technology in Cancer Research & Treatment)
To investigate the differences in serum tryptophan, lysine, and phenylalanine levels in breast cancer patients, the correlation between the three amino acids with the chemotherapy regimen, and their significance in the clinical diagnosis and treatment of breast cancer. Clinical data were collected from the Department of Breast Surgery at Yunnan Cancer Hospital, encompassing 216 cases from July to December 2020, including 91 healthy individuals, 38 with benign tumors, and 87 with cancer. Amino acid levels were measured using liquid chromatography-tandem mass spectrometry. Statistical analyses, such as the Kruskal-Wallis H-test and Wilcoxon test, were conducted to compare the levels of these amino acids across the healthy group, benign tumor group, and breast cancer group. The χ2 test and Fisher's exact probability method were employed to assess the relationship between amino acid levels and breast cancer stage, grade, and chemotherapy regimen. The results indicated that there were significant differences in serum lysine (H = 36.13, P  < .001) and phenylalanine (H = 34.03, P  < .001) levels among the three groups. However, tryptophan levels did not show statistically significant variances. Specifically, lysine and phenylalanine levels were significantly different when comparing the healthy group with the breast cancer group and the benign tumor group with the breast cancer group. These differences were not significant when comparing the healthy group with the benign tumor group. Furthermore, there were no statistically significant distinctions observed in lysine (F = 0.836, P  > .05) and phenylalanine (F = 1.466, P  > .05) levels across different conventional chemotherapy regimens among the breast cancer cases studied. Serum lysine and phenylalanine levels might serve as potential biomarkers for breast cancer, and the choice of chemotherapy regimen is unlikely to impact significant changes in these amino acid levels.